Rancang Bangun Alat Penyiram Tanaman Otomatis Menggunakan Sistem IoT pada Tanaman Bonsai - Dandi Azhari; Muhammad Hidayatullah; Paris Ali Topan; Desi Maulidyawati (Program Studi Teknik Elektro, 2024)
Bonsai plants are miniature trees that require care and water for their growth process. Watering the plants still uses manual watering techniques which are carried out at certain time intervals where sometimes the volume of water and the time of watering are not appropriate which causes disruption to the growth of the plants. The aim of this research is to create a time-based automatic plant watering system that can monitor soil moisture levels remotely. The method used is a quantitative experimental method which is preceded by an observation step followed by the design of an automatic watering system. Capacitive soil moisture sensors are used to monitor soil moisture levels. Real Time Clock (RTC) is used to run the timing functions that control the system. If the time has reached the predetermined limit, the system will send a notification via the Telegram application that the tool has worked automatically. Based on the research results, the data sent by the system to the telegram application is in the form of soil moisture values. At 7.00 the system works with a soil moisture value of 56% and at 7.05 the system stops working with a soil moisture value of 66%. At 16.00 the system will work with a soil moisture value of 59% and at 16.05 the system will stop working with a soil moisture value of 67%. In general, this system can work well and efficiently.